Unlike road deaths, smoking kills silently - Abd Razak, Dzulkifli (2006)
It only gets worse. The recent Ops Sikap,the joint police and Road Transport Department operations to help curb road accidents during the recent festive holidays, saw more accidents than last year. During the 11th Ops Sikap mounted during the DeepaRaya holidays, 228 people died in 15,716 accidents. During last year's DeepaRaya season, 13,661 accidents were recorded with 233 deaths. Of the deaths this year, about 70 per cent were motorcyclists and their pillion riders, followed by car drivers and passengers, and pedestrians. Compounding the problem this time around were drivers and riders using drugs. The federal traffic police chief said 113 motorists, including motorcyclists and commercial bus drivers, tested positive for morphine, heroin and ganja while they were on the road during Ops Sikap XI.